The effect of deformation on two-phase flow through proppant-packed fractured shale samples: A micro-scale experimental investigation. (July 2017) - Arshadi, Maziar; Zolfaghari, Arsalan; Piri, Mohammad; Al-Muntasheri, Ghaithan A.; Sayed, Mohammed
Highlights: Multiphase flow and geometrical deformation mechanisms are responsible for permeability reduction. Higher embedment and medium deformation were observed in samples with thinner proppant packing. Significant embedment in non-uniform mono-layer proppant packs may cause early production loss. Abstract: We present the results of an extensive micro-scale experimental investigation of two-phase flow through miniature, fractured reservoir shale samples that contained different packings of proppant grains. We investigated permeability reduction in the samples by conducting experiments under a wide range of net confining pressures. Three different proppant grain distributions in three individual fractured shale samples were studied: i) multi-layer, ii) uniform mono-layer, and iii) non-uniform mono-layer. We performed oil-displacing-brine (drainage) and brine-displacing-oil (imbibition) flow experiments in the proppant packs under net confining pressures ranging from 200 to 6000  psi. The flow experiments were performed using a state-of-the-art miniature core-flooding apparatus integrated with a high-resolution, X-ray microtomography system. We visualized fluid occupancies, proppant embedment, and shale deformation under different flow and stress conditions. We examined deformation of pore space within the proppant packs and its impact on permeability and residual trapping, proppant embedment due to changes in net confining stress, shale surface deformation, and disintegration of proppant grains at high stress conditions. In particular, geometrical deformation and two-phase flow effects within the proppant pack impacting hydraulic conductivity of the medium were probed. A significant reduction in effective oil permeability at irreducible water saturation was observed due to increase in confining pressure. We propose different mechanisms responsible for the observed permeability reduction in different fracture packings. Samples with dissimilar proppant grain distributions showed significantly different proppant embedment behavior. Thinner proppant layer increased embedment significantly and lowered the onset confining pressure of embedment. As confining stress was increased, small embedments caused the surface of the shale to fracture. The produced shale fragments were then entrained by the flow and partially blocked pore-throat connections within the proppant pack. Deformation of proppant packs resulted in significant changes in waterflood residual oil saturation. In-situ contact angles measured using micro-CT images showed that proppant grains had experienced a drastic alteration of wettability (from strong water-wet to weakly oil-wet) after the medium had been subjected to flow of oil and brine for multiple weeks. Nanometer resolution SEM images captured nano-fractures induced in the shale surfaces during the experiments with mono-layer proppant packing. These fractures improved the effective permeability of the medium and shale/fracture interactions.